Agreement on Cause of Death Between Proxies, Death Certificates, and Clinician Adjudicators in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study - Halanych, Jewell H. (Oxford University Press, 2011)
Death certificates may lack accuracy and misclassify the cause of death. The validity of proxy-reported cause of death is not well established. The authors examined death records on 336 participants in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study, a national cohort study of 30,239 community-dwelling US adults (2003–2010). Trained experts used study data, medical records, death certificates, and proxy reports to adjudicate causes of death. The authors computed agreement on cause of death from the death certificate, proxy, and adjudication, as well as sensitivity and specificity for certain diseases. Adjudicated cause of death had a higher rate of agreement with proxy reports (73%; Cohen's kappa (κ) statistic = 0.69) than with death certificates (61%; κ = 0.54). The agreement between proxy reports and adjudicators was better than agreement with death certificates for all disease-specific causes of death. Using the adjudicator assessments as the “gold standard,” for disease-specific causes of death, proxy reports had similar or higher specificity and higher sensitivity (sensitivity = 50%–89%) than death certificates (sensitivity = 31%–81%). Proxy reports may be more concordant with adjudicated causes of death than with the causes of death listed on death certificates. In many settings, proxy reports may represent a better strategy for determining cause of death than reliance on death certificates.